Preventing SQL Injection Attacks Using a Cryptography Technique - Radjai, Marwan (Faculty of Mathematics and Informatics- Unviversity Mohamed MOHAMED - M’SILA, 2016)
With the spread of Internet use in the world, security threats in the Internet increased dramatically. Among the vulnerabilities of the web application is SQL injection, which is based on the insertion of malicious requests to the DBMS, which executes these requests denier allowing access to sensitive and confidentiel data. The purpose of this research paper is to find the best way to protect Web applications and sensitive data against hackers and security breaches through the use of effective encryption systems which, in turn, provide a significant degree of protection for Web applications. We made a thorough study of the different optimal strategies based on encryption in their content. We dealt with the e-Signature and its effective role in the protection of data. We applied encryption algorithms such as ECC, NTRUand of some of the techniques used to protect and prevent contaminated queries that are entered by the attacker.
Keywords: ECC, RSA, SQL, SQLI, NTRU, Elgmal, PHPMyadmin.